Talent Management Strategies And Their Impact On Employee Retention - Klemens Mere (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
Talent management refers to the systematic attraction, development, retention, and deployment of individuals with high potential and value to the organization. The purpose of this study is to analyze talent management strategies and their impact on employee retention. This study adopts a literature review methodology to explore and synthesize existing research on the relationship between talent management strategies and employee retention. The literature review method is particularly suitable for gaining a comprehensive understanding of a topic by systematically collecting, analyzing, and interpreting previous studies, theories, and empirical findings. This study has demonstrated that talent management strategies play a crucial role in influencing employee retention. Through the review of relevant literature, it is evident that organizations that implement well-structured talent management practices—such as leadership development, career advancement opportunities, performance management, employee engagement initiatives, and continuous learning programs—are more successful in retaining high-performing employees.